(untitled) (American Journal of Human Ecology, 2015)
Perceptions and understanding of rural agroforest farmers about climate change, the possible consequences of cli-mate change and available adaptation options for its mitigation in the tropics have been noted to be abysmally low. This study examines the perception and adaptation strategies of agroforest farmers towards climate change mitigation in Ekiti State. The study area was stratified into two vegetation zones (rainforest and derived savannah). Pre-tested interview schedule were administered to eighty randomly selected agroforest farmers for collection of data in the two zones. Field observations revealed that majority of the respondents are married (96.25 %) male (93.75 %) of over 40 years old (81.25 %) with 50 % of them having more than 10 years of farming experience. The study revealed that farmers perceived that there are changes in climatic parameters (temperature, rainfall and wind intensity) with its attendant consequences on their production. Measures such as mulching, adjustment in planting period and planting of different crop were employed by respondents to mitigate the effect of climate change on their livelihood. The study also identified among others; lack of water for irrigation and lack of information on weather forecast as some of the problems militating against their adaptation to climate change.